Two new bamboo-feeding species of the genus Neocarpia Tsaur & Hsu (Hemiptera: Fulgoromorpha: Cixiidae: Eucarpiini) from Guizhou Province, China - Zhang, Pei; Chen, Xiang-Sheng (Zootaxa, 2013)
Two new bamboo-feeding species of the cixiid planthopper genus Neocarpia Tsaur & Hsu, 2003 (Hemiptera: Fulgoro-morpha: Cixiidae: Eucarpiini), N. bidentata sp. nov. (Guizhou: Xishui) and N. hamata sp. nov. (Guizhou, Yanhe), from southwest China, are described and illustrated. The generic characteristics are redefined. A key and a checklist to the known species of this genus in the world are provided.